Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1520/jfs14688j
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprint Enhancement Revisited and the Effects of Blood Enhancement Chemicals on Subsequent Profiler Plus™ Fluorescent Short Tandem Repeat DNA Analysis of Fresh and Aged Bloody Fingerprints

Abstract: This study was aimed at determining the effect of seven blood enhancement reagents on the subsequent Profiler Plus™ fluorescent STR DNA analysis of fresh or aged bloody fingerprints deposited on various porous and nonporous surfaces. Amido Black, Crowle's Double Stain, 1,8-diazafluoren-9-one (DFO), Hungarian Red, leucomalachite green, luminol and ninhydrin were tested on linoleum, glass, metal, wood (pine, painted white), clothing (85% polyester/15% cotton, 65% polyester/35% cotton, and blue denim) and paper (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 42 publications
3
43
0
3
Order By: Relevance
“…The amount of blood detected varied according to the case in which the endodontic file was collected, agreeing with the findings of Frégeau et al 24 who reported that luminol could be used to detect the presence of very small quantities of blood or blood stains diluted up to a 1:10 6 ratio.…”
Section: Discussionsupporting
confidence: 88%
“…The amount of blood detected varied according to the case in which the endodontic file was collected, agreeing with the findings of Frégeau et al 24 who reported that luminol could be used to detect the presence of very small quantities of blood or blood stains diluted up to a 1:10 6 ratio.…”
Section: Discussionsupporting
confidence: 88%
“…There is some evidence to suggest that inhibition has a greater impact on extremely low template samples [20] or is observed as a function of time between presumptive testing and STR profiling [21,22]. Given these observations, the data presented supports the use of ParaDNA technology on high template and medium template samples, which in the context of the present study would include the blood, saliva and semen stains.…”
Section: Resultssupporting
confidence: 50%
“…Tragove nastale prijenosom krvi dodirom na drugi predmet nazivamo otisci ili brisotine 16,17 . Na taj se način mogu prenijeti otisci prstiju, dlana, stopala, gume vozila te mogu imati individualne značajke, što može pomoći u identifikaciji počinitelja kaznenog djela 18 . Brisanjem ili slučajnim povlače-njem dijela tijela ili predmeta po drugom dijelu tijela ili predmeta nastaju brisotine 19,20 .…”
Section: Oblici Tragova Krviunclassified